(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Teaching is the one profession that creates all other professions. Many people know their target language, but they cannot use them communicatively. Still, they suffer from using target language. Throughout the years, teachers have been using several methods to teach students. In order to analyze students’ interaction, I did a research on teaching and learning process in Direct and Audio-Lingual method. The importance of my research is students’ ability to use language communicatively.